DINAMIKA PARTISIPASI ANGKATAN KERJA PEREMPUAN - Wulan Kurniasari; Toto Gunarto; Dedy Yuliawan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Women's participation in the labor force plays a crucial role in a country's economic growth. However, the gender gap in labor is still quite high in Indonesia. Female labor force participation rate tends to stagnate and lag behind men for the last 30 years, it’s indicating that there is a need improvement in employment. This research aims to test the factors that influence the female labor force participation rate in Indonesia from 1990 to 2021. Using multivariable regression analysis using the Ordinary Least Square method, it was found that there was a positive effect on education and female labor force participation rate. Meanwhile, fertility and working-age population have a negative effect on female labor force participation rate in Indonesia. Women’s labor force participation should be part of a policy strategy to maximize women's potential.